2022
DOI: 10.1007/s11469-021-00720-x
|View full text |Cite
|
Sign up to set email alerts
|

Protective Factors for Decreasing Nicotine, Alcohol, and Cannabis Use Among Adolescents with a History of Adverse Childhood Experiences (ACEs)

Abstract: Adolescents who have experienced adversity have an increased likelihood of using substances. This study examined if individual-, family-, school-, and community-level protective factors were associated with a decreased likelihood of substance use. Data from the Well-Being and Experiences Study (the WE Study) collected from 2017 to 2018 were used. The sample was adolescents aged 14 to 17 years (N = 1002) from Manitoba, Canada. Statistical methods included descriptive statistics and logistic regression models. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…The causes of adolescent IA are widespread and complex [ 2 , 25 ]. Among various intrapersonal factors, an individual’s childhood traumatic experience is the highest risk factor for adolescent IA [ 26 ]. Childhood trauma is a global phenomenon [ 27 , 28 ], and can cause serious psychological damage to an individual, leading to anxiety, depression, and other emotional and addictive behaviors [ 21 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The causes of adolescent IA are widespread and complex [ 2 , 25 ]. Among various intrapersonal factors, an individual’s childhood traumatic experience is the highest risk factor for adolescent IA [ 26 ]. Childhood trauma is a global phenomenon [ 27 , 28 ], and can cause serious psychological damage to an individual, leading to anxiety, depression, and other emotional and addictive behaviors [ 21 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may include assessing protective factors in the educational context such as the quality of the student–teacher relationship, students’ sense of belonging and connection to the school community and environment, and other important protective factors such as the quality of the parent–child relationship and children’s secure attachment to their caregivers. Previous research has found these factors to reduce risk among adolescents with an ACE history in other important domains (i.e., substance use), and they may also be important in fostering better education outcomes [ 28 ]. Moreover, the identification of protective factors may assist in the development of school-based interventions for children and adolescents with a history of childhood adversity that may be at risk for academic challenges in similar geographical contexts and social locations.…”
Section: Discussionmentioning
confidence: 99%
“…Data for this study are from the Well-being and Experiences (WE) Study, an intergenerational and longitudinal cohort study of parent–adolescent dyads from Winnipeg, Manitoba, a mid-sized Canadian city, and surrounding communities. A detailed description of the WE Study recruitment methods and study design has been published previously [ 24 , 27 , 28 ]; however, in brief, the sampling design used random-digit dialling (21%) and convenience sampling (79%), including referrals and community advertising. No differences were found for several variables between groups based on recruitment methods (e.g., household income, ACEs).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations